Environmental Conditions and Seasonal Variables in American Youth Football Leagues. (November 2017) - Yeargin, Susan W.; Cahoon, Erin; Hosokawa, Yuri; Mensch, James M.; Dompier, Thomas P.; Kerr, Zachary Y.
Our study describes youth football (YFB) environmental conditions and the associated heat index (HI) risk category. An observational research design was utilized. Independent variables included month, time, event, and geographic location. Main outcome variables were frequency of events, average HI, and corresponding risk categorization. The HI was recorded with the day and time for each YFB event across 2 YFB seasons. Nearly half (49.8%) of events were in a high HI risk category and 20.0% should have been cancelled. The hottest HI values were recorded in July and August (83.2 ± 9.4°F to 87.2 ± 10.9°F; 24.0% of YFB events). The 7 to 10am time frame was cooler (67.7 ± 14.5°F; 6.3% of YFB events) than other time frames ( P < .001). Hotter HI values were recorded in practices versus games (75.9 ± 14.1°F vs 70.6 ± 14.6°F; t = −6.426, P < .001). Starting the YFB season in September and holding weekend events in the early morning hours can decrease exposure to environmental heat stress.